2000
DOI: 10.1152/jn.2000.83.6.3509
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Synaptic Interactions Between Intercalated Neurons of the Amygdala

Abstract: The intercalated (ITC) cell masses are small GABAergic cell clusters interposed between the basolateral (BL) complex and central (CE) nucleus of the amygdala. ITC cells receive excitatory afferents from the BL complex and generate feed-forward inhibition in the CE nucleus. Recently it was shown that ITC cells could gate impulse traffic between the BL complex and CE nucleus in a spatiotemporally differentiated manner. In addition, it was hypothesized that lateromedial inhibitory interactions between different I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 21 publications
8
95
0
Order By: Relevance
“…For example, GABAergic cells within intercalated cell masses (ICM), which lie at the anatomical interface of the BLA and CeA, generate feedforward inhibition of CeA neurons in response to BLA activation (Royer et al, 1999(Royer et al, , 2000, and are regulated by extrinsic glutamatergic afferents from the prefrontal cortex and dopaminergic afferents from the ventral midbrain (Bissiere et al, 2003;. Therefore, cannabinoid actions within these regions, which are known to occur (French et al, 1997;Gessa et al, 1998;Auclair et al, 2000;Patel and Hillard, 2003), could modulate CeA activity independently of the BLA, via modulation of ICM neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GABAergic cells within intercalated cell masses (ICM), which lie at the anatomical interface of the BLA and CeA, generate feedforward inhibition of CeA neurons in response to BLA activation (Royer et al, 1999(Royer et al, , 2000, and are regulated by extrinsic glutamatergic afferents from the prefrontal cortex and dopaminergic afferents from the ventral midbrain (Bissiere et al, 2003;. Therefore, cannabinoid actions within these regions, which are known to occur (French et al, 1997;Gessa et al, 1998;Auclair et al, 2000;Patel and Hillard, 2003), could modulate CeA activity independently of the BLA, via modulation of ICM neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Amano et al (2011) have shown that the two sub-regions within BA, the lateral part (BL), and the medial part (BM), act in concert to express fear but possess a certain amount of redundancy between themselves. Similarly, there are two different ITC cell clusters and they are thought to contribute differentially to the expression of fear and extinction memories (Royer et al, 2000;Pape and Paré, 2010). The output nucleus Ce also has distinct sub-circuits with different functions in fear learning (Coicci et al, 2010;Haubensak et al, 2010).…”
Section: Fear Conditioning Protocolmentioning
confidence: 99%
“…The amygdala intercalated cells (ITC; fig 2) are distributed along the lateral and medial parts of the basolateral amygdaloid complex. The more dorsally located ITC clusters receive glutamatergic excitatory input from LA and BA, while the medial ITC clusters receive GABAergic inhibition from the dorsal ITC clusters and excitation from BA; the medial clusters, in turn, inhibit Ce, the output station in the amygdala (Paré and Smith, 1993a,b;Royer et al, 1999;Royer et al, 2000;Jungling et al, 2008). This strategic location of the medial ITC clusters, between the sensory input (BLA) and fear output (Ce) stations of the amygdala, is thought to be critical for regulating classically conditioned fear responses (Paré et al, 2004).…”
Section: B Modeling the Network Of Amygdala Intercalated Cells (Li Ementioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the role of TRPC5 in synaptic transmission at excitatory inputs to intercalated cells (Royer et al, 2000). Residing in a narrow strip of cellular clusters between the BLA complex and the central nucleus of the amygdala (CeA), they receive synaptic inputs from the lateral and basal nuclei and project to the CeA.…”
Section: Synaptic Transmission and Ltp In Cortical And Thalamic Inputmentioning
confidence: 99%